An Opportunity During Antenatal Services to Strengthen Nurturing Care: Global and National Recommendations for Routine Ultrasound Before 24 Weeks Gestation - Slemming, Wiedaad; Drysdale, Roisin; Richter, Linda M. (Frontiers in Public Health, 2021)
Introduction: The Healthy Pregnancy, Healthy Baby study (HPHB) augments a routine service (pregnancy ultrasound), with information about fetal and infant development and the importance of parent wellbeing and infant care, to assess whether it will improve child development and growth, parent-infant attachment, parental wellbeing and routine clinic attendance. This paper outlines the process of intervention development, adaptation and implementation in a complex environment with multiple stakeholders. Methods: Study participants were recruited from pregnant women attending fetal ultrasound (US) at Chris Hani Baragwanath Hospital (CHBH), Soweto, South Africa, were randomized to intervention or control arms. Partners were invited to attend all sessions. The intervention arm received ultrasound images, a Baby Booklet containing key messages about fetal and infant development and a space to affix the US image and a photograph of the procedure. The intervention is being tested through a randomized controlled trial with outcome assessments at 6 weeks and 6 months follow-up. Results: Formative research informed the design and content of the intervention materials. Implementation is monitored through weekly reports and team meetings as well as formal and informal feedback received from staff and participants. Close collaborations with clinicians enhanced recruitment practices and provided clinical oversight of the trial procedures. Ongoing stakeholder engagement informed intervention procedures and strategies to address challenges that arise during trial implementation. Conclusion: This study emphasizes the importance of dynamic, inclusive and interactive approaches to intervention development and implementation, as well as the purposeful use of varied information from diverse sources in decision-making for effective implementation.